A comparative study of propofol alone and propofol combined with midazolam for dental treatments in special needs patients. Issue 22 (4th June 2021) - Lin, I-Hsin; Huang, Mao-Suan; Wang, Pei-Yu; Huang, Ta-Sen; Chong, See-Yen; Chen, Sam Li-Sheng; Tsai, Hung-Huey
Abstract : Abstract: Although dental treatment with sedation is performed increasingly in special needs patients, data on adding midazolam to intravenous propofol sedation are very limited for this group. The purpose of this study was to identify the factors and procedure time associated with the use of intravenous sedation with propofol alone or propofol combined with midazolam in dental patients with special needs. This was a retrospective data analysis. The sedation medications and relevant covariates, including demographic parameters, disability levels, oral health conditions, dental procedures, treatment time, and side effects, of 718 patients with special needs were collected between April 2013 and September 2014. The unfavorable side effects by sedation types were reported. Factors associated with procedure time and the sedation medications were assessed with multiple logistic regression analyses. Of 718 patients, 8 patients experienced unfavorable side effects (vomiting, sleepiness, or emotional disturbance) after the dental procedures; the rate was 0.6% in the 509 patients who received propofol only. In 209 patients who received propofol and midazolam, 2.4% experienced the side effects. Sedation time was associated with body mass index (BMI) < 25 (adjusted odds ratio [aOR] = 1.45, 95% confidence interval [CI]: 1.04–2.04) and the performance of multiple dental procedures (aOR = 1.44, 95% CI: 1.06–1.97) but not associated with the sedation types. A significant odds ratio for the combined use of propofol and midazolam was shown for adolescents (aOR = 2.22, 95% CI: 1.28–3.86), men (aOR = 2.05, 95% CI: 1.41–2.98), patients with cognitive impairment (aOR = 1.99, 95% CI: 1.21–3.29), and patients undergoing scaling procedures (aOR = 1.64, 95% CI: 1.13–2.39). With the acceptable side effects of the use of propofol alone and propofol combined with midazolam, multiple dental procedures increase the sedation time and the factors associated with the combined use of propofol and midazolam are younger age, male sex, recognition problems, and the type dental procedure in the dental treatment of patients with special needs.